Challenge stressors as a motivational tool female employees in the Mongolian banking sector - Enkhjav, Tumentsetseg; Imola, Csehné Papp; Varga, Erika (Journal of Eastern European and Central Asian Research (JEECAR), 2020)
In this study, the relationship between challenge stressors and burnout was examined to find out whether the challenge stressors can be one of the root causes of burnout among Mongolian female employees in the banking sector. As the service industry contributes to more than 50 percent of GDP in Mongolia, most employees in the financial sector are females; the adaption of smart technologies in this sector is thriving. Therefore, the first objective was to reveal whether there is a significant relationship between challenge stressors and burnout. The second objective was to test whether challenge stressors are inversely related to burnout and its three dimensions. A quantitative design was applied, and 101 validated questionnaires were analyzed. Overall, approximately 4% of the variance in burnout can be predicated by challenge stressors. A significant and positive association between challenge stressors and burnout (its two dimensions: emotional exhaustion and depersonalization) was found.